Tourism in Gorkha: A proposition to Revive Tourism After Devastating Earthquakes - Ghimire, Him Lal (Journal of Tourism and Hospitality Education, 2016)
Gorkha, the epicenter of devastating earthquake 2015 is one of the important tourist destinations of Nepal. Tourism is vulnerable sector that has been experiencing major crises from disasters. Nepal is one of the world’s 20 most disaster-prone countries where earthquakes are unique challenges for tourism. Nepal has to be very optimistic about the future of tourism as it has huge potentials to be the top class tourist destinations by implementing best practices and services. Gorkha tourism requires a strategy that will help manage crises and rapid recovery from the damages and losses. This paper attempts to explain tourism potentials of Gorkha, analyze the impacts of devastating earthquakes on tourism and outline guidelines to revive tourism in Gorkha.Journal of Tourism and Hospitality Education (Vol. 6), 2016, Pages: 67-94